THE DIVISION OF LANGUAGE UNITS INTO NOTION AND FUNCTION WORDS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
The article provides information about the division of language units into notion and function words. It is a fundamental aspect of linguistic structure and cognitive processing. This distinction plays a crucial role in organizing and conveying meaning within languages, involving theoretical perspectives, typological variations, psycholinguistic and cognitive implications, language acquisition and development, as well as pedagogical considerations. The discussion of this linguistic division encompasses the examination of universal and language-specific patterns in the distribution and use of notion and function words, offering insights into the range of grammatical and communicative strategies employed by human languages. And detailed information is provided in the article.